The Role of Helmet Use on Severity and Pattern of Maxillofacial Injuries Among Motorcycle Crash Victims Attending Mulago Hospital, Uganda - Joses O. Komakech; Isaac Okullo; Francis Lakor; Charles Mugisha Rwenyonyi (Journal of Dentistry And Oral Implants, 2017)
The objective of the study was to establish the role of helmet use on severity and pattern of maxillofacial injuries among motorcycle crash victims attending Mulago Hospital. This was descriptive cross sectional case series study using a questionnaire in form of an oral interview, clinical examination and review of medical records of the patients. The pattern of injuries was assessed based on the demarcated regions of the face. The severities of the injuries were scored using the Facial Injury Severity Scale. The data were analysed using SPSS version 17.0. There were 105 participants (male/female: 97/8) aged 15 to 63 years. Most participants (n= 74, 70.5%) were riders and the rest were passengers. There were no female riders. Most participants were from Kampala and surrounding districts. Overall, 35.2% of the participants had helmets: 50% of the riders and 0% of the passengers. About 73% o the participants used Three Quarter Shell helmet design. There was no significant difference in the pattern of injuries between the passengers and non helmeted riders (p=0.076). There was a higher frequency helmeted riders (n = 15, 40.5%) with pan-facial fractures compared to other participants. Non helmeted riders and passengers had significantly more injuries to the lower two thirds of the face compared to the helmeted riders. Passengers had less severe facial injuries compared to riders. We conclude that about a third of the participants who were riders used helmets, being particularly the Three Quarter Shell design. The helmeted riders had more severe maxillofacial injuries and of panfacial category as compared to other participants. The passengers had least severe injuries compared to riders. It is recommended to carry out further studies to elucidate on motorcycle related maxillofacial injuries especially in regard to the quality of helmets and their adequate use.
Keywords: FISS